Accelerating the implementation of the Sustainable Development Goals at the local level: Unpacking governance processes and tensions - Magdalena Bexell; Basil Bornemann; Enayat A. Moallemi; Ha B. Vien (Earth System Governance)
Despite a growing body of research on the role of the Sustainable Development Goals (SDGs) at the local level, knowledge on how they are taken up in local governance processes remains limited. This article contributes to knowledge on SDG implementation by examining how the SDGs can contribute to governance change at the local level. We develop a process-oriented analytical framework that examines SDG-induced governance change along four stages: how the SDGs affect local governance arrangements (exposure), set them in motion (resonance), and change their structures (adaptation) and mode of operation (transformation). On this basis, we analyze existing empirical case studies to identify patterns of SDG-induced governance change, as well as facilitating and constraining factors. We identify three overarching tensions - between global aspirations and local realities, institutional continuity and change, and long-term and short-term policy horizons, that shape SDG-induced local governance change and must be navigated to accelerate SDG implementation.